HEMATOLOGICAL DISORDERS OF PROPYLTHIOURACIL IN THYROID PATIENTS AT TERTIARY CARE HOSPITAL OF HYDERABAD - Uzma Naz Shaikh (Army Medical College Rawalpindi, 2021)
Objective: To find out the frequency of anemia, agranulocytosis and thrombocytopenia in hyperthyroid patients after the use of propylthiouracil.